Electrical and Thermal Conduction Behaviors in La‐Substituted GdBaCuFeO5+δ Ceramics. Issue 10 (8th July 2015) - Zeng, Chengcheng; Zhan, Bin; Butt, Sajid; Liu, Yaochun; Ren, Guangkun; Lin, Yuan‐Hua; Li, Ming; Nan, Ce‐Wen
Abstract : Gd1− x La x BaCuFeO5+δ polycrystalline ceramics have been prepared by a sol–gel method combined with the traditional ceramic processing. Analysis of the microstructure and phase composition reveals that the pure GdBaCuFeO5+δ phase can be obtained even after the substitution of 50% La at Gd‐site. The band gap can be tuned from 1.47 to 1.36 eV by La substitution, resulting in a significant increase in the electrical conductivity. In addition, the total thermal conductivity can also be suppressed by the substitution of La at Gd‐sites. A ZT value of 0.02 at 1023 K is achieved in the 50% La‐substituted samples, which is over 20 times higher than that of the pure GdBaCuFeO5+δ sample.